Pheochromocytoma in a Twelve-Year-Old Girl with SDHB-Related Hereditary Paraganglioma-Pheochromocytoma Syndrome - Graham, Daryl (Hindawi Publishing Corporation, 2014)
A twelve-year-old girl presented with a history of several weeks of worsening headaches accompanied by flushing and diaphoresis. The discovery of markedly elevated blood pressure and tachycardia led the child's pediatrician to consider the diagnosis of a catecholamine-secreting tumor, and an abdominal CT scan confirmed the presence of a pheochromocytoma. The patient was found to have a mutation in the succinyl dehydrogenase B (SDHB) gene, which is causative for SDHB-related hereditary paraganglioma-pheochromocytoma syndrome. Herein, we describe her presentation and medical management and discuss the clinical implications of SDHB deficiency.